2nd Annual Meeting of the Australian Chapter of the Controlled Release Society, Canberra 2009 - Toth, Istvan (Current Drug Delivery, 2009)
The Australian Chapter of the Controlled Release Society (AUS-CRS) is dedicated to broadening the awareness, application and appeal of controlled release of bioactive molecules and technology within the academic and industrial community. Another important purpose of the Chapter is to support young researchers in the field of drug delivery and formulation. Successful delivery of a high quality annual scientific meetings and workshops provides the principal means for achieving these aims. Our 2nd AUS-CRS Annual Meeting was held in conjunction with Australasian Pharmaceutical Science Association (APSA) Conference on Sunday 7th of December 2008 at the Australian National University in Canberra. Created in July 2007, AUSCRS is only a young chapter of the main international CRS organization, yet the quality of the program was clearly excellent. Outstanding plenary lectures were given by highly recognized drug delivery scientists.